Komunikasi Dakwah dalam Kampanye Hijrah di Media Sosial Instagram - Cyinthia Ayu Meilani Setiawan; Dedeh Fardiah; Irfan Safrudin (Jurnal Inovasi Komunikasi, 2025)
Abstract. Instagram has become a social media platform that is currently used not only for business purposes but also to spread goodness through da'wah. The large number of da'wah accounts popping up on Instagram has become a special attraction for people who want to learn more about Islamic teachings. The purpose of this study is to determine the da'wah strategy, the content of da'wah messages, and the da'wah methods used by the @teladan.rasul account in campaigning for hijrah on Instagram using a qualitative approach with a case study method. The results of this study show that the da'wah strategies, message content, and da'wah methods are carefully prepared according to the dominant target followers, which is what makes followers interested in choosing and following the @teladan.rasul account as a supporting medium for the hijrah process they are undertaking, thereby gradually applying the message content conveyed through concrete actions in their lives.